2015
DOI: 10.3389/fphys.2015.00337
|View full text |Cite
|
Sign up to set email alerts
|

Both Orai1 and TRPC1 are Involved in Excessive Store-Operated Calcium Entry in Striatal Neurons Expressing Mutant Huntingtin Exon 1

Abstract: It has been previously reported that N-terminus of mutant huntingtin (product of the 1st exon) is sufficient to cause a Huntington's disease (HD) pathological phenotype. In view of recent data suggesting that improper regulation of store-operated calcium (SOC) channels is involved in neurodegenerative processes, we investigated influence of expression of the mutant huntingtin N-terminal fragment (Htt138Q-1exon) on SOC entry (SOCE) in mouse neuroblastoma cells (Neuro-2a) and in primary culture of medium spiny n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 42 publications
4
52
0
1
Order By: Relevance
“…In our study, NOX2 activation by dRP leads to NF-κB activation (as shown by several approaches, including p65-NF-κB translocation and phosphorylation), which appears critical in the proangiogenic signaling cascade triggered by dRP. The role of NF-κB in the signaling cascade stimulated by dRP was demonstrated using both the QNZ inhibitor [which not only has low nanomolar potency on NF-κB but can also inhibit store-operated calcium channels at high nanomolar concentrations ( 68 )] and genetic silencing of p65-NF-κB. This is in agreement with recent studies showing activation of NF-κB downstream of NOX2 in angiogenic responses of endothelial cells ( 40 ).…”
Section: Discussionsupporting
confidence: 85%
“…In our study, NOX2 activation by dRP leads to NF-κB activation (as shown by several approaches, including p65-NF-κB translocation and phosphorylation), which appears critical in the proangiogenic signaling cascade triggered by dRP. The role of NF-κB in the signaling cascade stimulated by dRP was demonstrated using both the QNZ inhibitor [which not only has low nanomolar potency on NF-κB but can also inhibit store-operated calcium channels at high nanomolar concentrations ( 68 )] and genetic silencing of p65-NF-κB. This is in agreement with recent studies showing activation of NF-κB downstream of NOX2 in angiogenic responses of endothelial cells ( 40 ).…”
Section: Discussionsupporting
confidence: 85%
“…In accordance, the Orai1 gene has been reported as one of the six candidate genes that could be responsible of the neurological phenotypes found in inherited microdeletion syndromes caused by a 445 kb chromosomal deletion [66]. Also, defective SOCE have been associated to severe brain disorders where stem cell dysfunctions have been reported like neurodegenerative Alzheimer's disease [67][68][69]. Conversely, increased SOC and STIM expression occurs in brain cancer cells that could arise from mutated NSC [70][71][72][73].…”
Section: Discussionmentioning
confidence: 88%
“…EVP4593 exerted a similar effect on MSN cells expressing an N-terminal fragment of mHtt [16]. Now, EVP4593 is proven to act as an inhibitor of SOCE necessary for the initial stages of the NF-κB signaling pathways; however, the molecular target of EVP4593 remains unknown.…”
Section: Calcium Dyshomeostasis In Hdmentioning
confidence: 99%
“…Cytofluorimetric measurements demonstrated that incubation of Neuro-2a cells (HD model) with EVP4593 results in increased survival of the cells [16]. …”
Section: Calcium Dyshomeostasis In Hdmentioning
confidence: 99%